Questions Related to the Equation of State of High-Density Matter - M. Coleman Miller (Universe, 2019)
Astronomical data about neutron stars can be combined with laboratory nuclear data to give us a strong base from which to infer the equation of state of cold catalyzed matter beyond nuclear density. However, the nuclear and astrophysical communities are largely distinct; each has their own methods, which means that there is often imperfect communication between the communities regarding caveats about claimed measurements and constraints. Here we present a brief summary from one astronomer’s perspective of relevant observations of neutron stars, with warnings as appropriate, followed by a set of questions that are intended to help enhance the dialog between nuclear physicists and astrophysicists.